2016
DOI: 10.1038/onc.2016.153
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the SDF1/CXCR4 pathway retards muscle atrophy during cancer cachexia

Abstract: Cancer cachexia is a life-threatening syndrome that affects most patients with advanced cancers and causes severe body weight loss, with rapid depletion of skeletal muscle. No treatment is available. We analyzed microarray data sets to identify a subset of genes whose expression is specifically altered in cachectic muscles of Yoshida hepatoma-bearing rodents but not in those with diabetes, disuse, uremia or fasting. Ingenuity Pathways Analysis indicated that three genes belonging to the C-X-C motif chemokine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…The study also showed that the levels of SDF1 isoforms were reduced in muscle of cachectic mice. 60 Although SDF1 did not meet the predefined cut-off for DASG, a similar trend was also observed in our study (down-regulated in cachectic cases when compared with WS cancer patients, data not shown). It would be interesting to further investigate if this pathway can be targeted for potential interventions for human CC.…”
Section: Skeletal Muscle Function and Differentiationsupporting
confidence: 87%
See 2 more Smart Citations
“…The study also showed that the levels of SDF1 isoforms were reduced in muscle of cachectic mice. 60 Although SDF1 did not meet the predefined cut-off for DASG, a similar trend was also observed in our study (down-regulated in cachectic cases when compared with WS cancer patients, data not shown). It would be interesting to further investigate if this pathway can be targeted for potential interventions for human CC.…”
Section: Skeletal Muscle Function and Differentiationsupporting
confidence: 87%
“…Our IPA analysis also predicted CXCR4 signalling pathways to be associated with CC. Martinelli et al ., recently showed that down‐regulation of genes involved in this pathway led to muscle wasting in Yoshida hepatoma‐bearing rodents and subsequent activation‐reduced muscle wasting. The study also showed that the levels of SDF1 isoforms were reduced in muscle of cachectic mice .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in skeletal muscle, Pak1 has been associated with the regulation of glucose uptake through insulin‐induced Glut4 translocation and in contraction modulation by phosphorylating Myosin Light Chain Kinase . In addition, we have recently shown that Pak1 is down‐regulated in atrophying gastrocnemius of Yoshida hepatoma‐bearing rats and others have reported it to be up‐regulated in soleus muscles following Axokine administration . All this evidence points to a central role of Pak1 in processes related to muscle physiology.…”
Section: Resultsmentioning
confidence: 71%
“…Cachexia appears in nearly 50% of patients with advanced stage of cancer and leads to progressive functional impairment, decreased quality of life with respiratory complications, and death can occur following the loss of ~75% of skeletal muscle mass . We have recently found that three genes encoding for proteins of the C‐X‐C motif chemokine receptor 4 pathway are down‐regulated in the atrophying gastrocnemius of Yoshida hepatoma‐bearing rats: stromal cell‐derived factor 1, adenylate cyclase 7, and p21 protein‐activated kinase 1 (Pak1) …”
Section: Introductionmentioning
confidence: 99%